Toxic elements levels and risk assessment in lung and Bhutan oyster mushrooms and their cultivation matrices - Konpong Boonyingsathit; Piyanut Sridonpai; Dunyaporn Trachootham; Nongnuch Sungayuth; Kunchit Judprasong (Journal of Agriculture and Food Research)
This study evaluated toxic element concentrations and associated health risks in two cultivated oyster mushroom species (Pleurotus pulmonarius and P. sajor-caju) in Thailand. Arsenic (As), cadmium (Cd), mercury (Hg), and lead (Pb) were quantified in fruiting bodies and substrates using ICP-QQQ-MS. Statistical analysis using one-way ANOVA (p < 0.05) confirmed species-specific differences in metal accumulation. Mean concentrations in mushrooms were below national and international limits: Pb ranged from 0.010 to 0.028 mg/kg, Cd 0.036–0.038 mg/kg, Hg 0.0031–0.0037 mg/kg, and As 0.019–0.028 mg/kg (wet weight). However, risk assessments revealed that children consuming large amounts could exceed safe exposure thresholds. The hazard quotient (HQ) for Cd and Hg remained below 1 in all groups (Cd: 0.002–0.259; Hg: 0.0005–0.0919). Inorganic arsenic exposure resulted in margin of exposure (MOE) values as low as 1.1 in children aged 3–5.9 years (97.5th percentile), indicating elevated risk. Lead exposure exceeded the U.S. FDA interim reference level in children consuming grilled or boiled P. pulmonarius (up to 114.9 % IRL). Substrate analysis showed that rubber-wood sawdust and rice bran contributed 77.9 % and 9.2 % of total Pb burden, respectively. Metal uptake was species-dependent: P. pulmonarius absorbed 9.7 % of As and 1.7 % of Pb from substrate, compared to 6.6 % and 0.6 % in P. sajor-caju. These findings emphasize the role of substrate quality and species selection in ensuring food safety. Enhanced monitoring and substrate control are recommended to minimize risk in sensitive populations.